FRAMING THE LIE: A LINGUISTIC ANALYSIS OF VIRAL FAKE NEWS DISCOURSE - Daulay, Sholihatul Hamidah; Aulia, Dea Nita; Zahra, Nazwa Atalia (BASIS (Bahasa dan Sastra Inggris), 2025)
In the digital era, fake news has become a powerful tool to influence public opinion, spread fear, and manipulate people's behavior. Language plays a significant role in this phenomenon, not only as a means of communication, but also as a tool of persuasion and misdirection. This article examines the linguistic strategies commonly used in the creation and spread of viral hoaxes, using a discourse analysis approach and framing theory. The focus lies on the use of emotional language, manipulative diction, hyperbole, metaphors, as well as narratives designed to establish false credibility and trigger strong emotional reactions. The article also discusses the constructive collaboration between language and visual elements such as images, memes and symbols that reinforce misleading narratives on social media. Data sources consist of 3-5 hoax news stories that have been clarified by fact-checking sites such as TurnBackHoax.id. Data collection was done through documentation techniques by downloading the hoax text and supporting information. Data analysis was conducted qualitatively through content analysis and comparison between the hoax text and its clarification. The findings of this article emphasize the importance of critical awareness of language and media literacy in dealing with disinformation, as well as the need for an interdisciplinary approach involving linguistics, communication, and digital media studies.